(untitled) (Revista Interdisciplinar Pensamento Científico, 2021)
This work approaches the judicialization’s effects on health when the Judiciary Power imposes on the State and health insurance the coverage of experimental medicines that are not registered in ANVISA, off label medicines, excluded procedures from the list of the ANS and medicines that are not on the list of Public Authorities, emphasizing the fact that health is a fundamental right provided in the Federal Constitution of 1988 and it should be feasible for all people without distinction, enabling them to live a dignified life. The difference in treatment given to the State and health insurance is evidenced when it comes to the provision of this experimental medicines, through the divergence of understanding between the jurisprudence and what is determined by the Law n°. 9.656 of 1998, which regulates private health insurance plans and insurance. The objective of this study is to understand the discretion and limits for judicial intervention in guaranteeing access to health care.